Study on prevalence of anemia in pregnant women in labour - Goyal, Neelam; Pandey, Harshita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: In the developing world Nutritional deficiency anaemia is the commonest finding in pregnant women. Lack of balanced diet, poor socio-economic status, repeated pregnancies and illiteracy are seen associated with Anaemia commonly. Anaemia itself results in maternal morbidities and poor pregnancy outcomes. Neonatal morbidities also have a direct equation with anaemia. It is a study done on pregnant women in labour with the sole objective to estimate the prevalence of anaemia amongst them and associated fetomaternal morbidities. Methods: It is a prospective observational study done on 300 pregnant women presenting in labour from October 2019-Decemebr 2019, in Government Doon Medical College, Dehradun. These women belonged to Dehradun and surrounding hilly areas of Uttarakhand. Their haemoglobin levels (complete blood count) were assessed at the time of admission along with other routine investigations. They were also assessed for associated pre and post-delivery morbidities and mortality. Results: In this study, out of 300 pregnant women presenting in labour from October 2019 to December 2019, in Government Doon Medical College Dehradun, the incidence of anaemia was found to be very high (70%). Severely anaemic patient group was found to have maximum number of fetomaternal complications and blood transfusion requirements. Conclusions: Despite all the maternal welfare programmes being run at National levels, it is being observed that there is a high unacceptable prevalence of anaemia in pregnant women. This increases their morbidity and mortality. It is a huge burden on hospital finances and blood bank for blood transfusions which are preventable. There is need to strengthen our health care system at primary level for pregnant women and teenage girls.